Pahiram ng isang umaga (Pasig City Regal Films)
Pahiram ng isang umaga revolves around Juliet, who finds herself struggling againts an ever-escalating series of problems. A determined single parent, she manages to raise a child while remaining successful in her career as an advertising executive. Everything in her life seems to go well until she is diagnosed with a terminal disease. For her son's sake, and without revealing her condition, she is forced to resolve her most important life relations, rekindling first her connection with her parents, and then with the very man who fathered her son. In the twilight of her life, she meet and falls in love with a beleaguered artist, Ariel, who is constantly depressed and perpetually contemplating suicide. She slowly loses her health but unknowingly reawaken Ariel's desire to live, and they both engage in a meaningful affair.
VCD
Vilma Santos, Gabby Concepcion, Eric Quizon, Zsa Zsa Padilla.
Keywords: Drama; Feature films